Climate Change and Horticulture Crop Production - Verma, Subhash C.; Thakur, Meena; Bhardwaj, S. K. (International Journal of Economic Plants, 2015)
Horticulture sector is the major component of agriculture and has experienced serious threat from climate change. The increase in temperature and variability in precipitation pattern has led to the development of abiotic stresses which are affecting the horticulture productivity. If climatic factors changes in a region beyond the tolerance of a species phenotypic plasticity, then distribution changes of the species may be inevitable. High temperature increase plant maturity rate, effect bud and flower development, fruit cracking, sun burn and upward shift of plants. Carbon dioxide is the prime substrate for photosynthesis and from plant perspective additional CO2 may be beneficial, but the interaction effect of elevated CO2 and higher temperature caused low yield of horticultural crops. Increased CO2 can also lead to increased carbon: nitrogen ratios in the leaves of plants or in other aspects of leaf chemistry, possibly changing herbivore nutrition. The chilling requirement for flowering of many ornamental plants is being affected by the melting of ice caps in Himalayan regions. High temperature leads to flower bud drop and unmarketable spikes in tropical orchids. Defensive mechanism in plants is lowered under stress conditions making them more susceptible to insect-pests. Therefore, attention should be given on development of adaptation technologies and quantify the mitigation potential of horticultural crops. Development of new cultivars tolerant to high temperature, resistant to insect-pests and diseases, short duration and producing good yield under stress conditions and judicious water utilization technologies should be the main strategies to meet the challenges of climate change.